Sanitary ceramic with reduced glaze pores and preparation method and application thereof

By adding calcium fluoride to the raw materials of the sanitary ceramic body and controlling the firing temperature gradient, the pore problem of sanitary ceramic glaze is solved, significantly reducing the number of pores and improving the quality and function of the glaze is improved.

CN119409480APending Publication Date: 2025-02-11JOMOO KITCHEN & BATHROOM
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411403945.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Pores often occur during the firing process of sanitary ceramic glaze, which affects the appearance and usage function. The existing methods such as selecting high-quality raw materials and extending the firing time are limited in effects.

Method used

By introducing 0.5-1.0 parts of calcium fluoride into the raw materials for preparing sanitary ceramic bodies and controlling the temperature gradient of the firing process, the active calcium oxide reacts with sulfur-containing impurities to form calcium sulfide, which reacts with oxygen at high temperatures. Release sulfur dioxide to prevent sulfide gas from forming pores on the glaze surface.

Benefits of technology

It significantly reduces the number of pores on the glaze surface of sanitary ceramics, improves the quality and use function of the glaze surface, and is especially suitable for sanitary ceramics with double-sided glazing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides sanitary ceramic with reduced glaze pores as well as a preparation method and application of the sanitary ceramic. The sanitary ceramic is prepared from the following materials in parts by weight: 10 to 20 parts of potassium feldspar, 15 to 25 parts of pyrophyllite, 10 to 20 parts of sericite, 20 to 30 parts of porcelain clay, 20 to 30 parts of kaolin, 5 to 10 parts of black mud, 0.5 to 1.0 part of wollastonite, 1.0 to 2.0 parts of dolomite and 0.5 to 1 part of calcium fluoride. The calcium fluoride is introduced into the raw materials for manufacturing the sanitary ceramic body, and the firing process is controlled, so that the number of pores in the glaze surface of the fired sanitary ceramic is remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sanitary ceramics, and in particular to a sanitary ceramic with reduced glaze pores and a preparation method and use thereof. Background Art

[0002] During the firing process, pores often appear on the glaze of sanitary ceramics. These pores affect the appearance of the glaze, often causing the product to be scrapped and affecting the usability of the glaze.

[0003] At present, the conventional method to reduce glaze pores is to select high-quality raw materials with less impurities, extend the kiln firing time, and increase the glaze melting temperature. However, high-quality resources are becoming increasingly scarce and expensive, while extending the firing time and adjusting the glaze have limited effects in reducing pores.

[0004] Therefore, there is a need for a sanitary ceramic with reduced glaze pores and a preparation method and use thereof. Summary of the invention

[0005] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.

[0006] In one aspect, the present application provides a sanitary ceramic with reduced glaze pores, the body of the sanitary ceramic being made of the following materials, which include, by weight, 10-20 parts of potassium feldspar, 15-25 parts of pyrophyllite, 10-20 parts of sericite, 20-30 parts of china clay, 20-30 parts of kaolin, 5-10 parts of black mud, 0.5-1.0 parts of wollastonite, 1.0-2.0 parts of dolomite and 0.5-1 parts of calcium fluoride.

[0007] In one embodiment, the material includes, by weight, 12-15 parts of potassium feldspar, 20-25 parts of pyrophyllite, 10-15 parts of sericite, 20-26 parts of china clay, 20-25 parts of kaolin, 5-10 parts of black mud, 0.5-1.0 parts of wollastonite, 1.0-1.5 parts of dolomite and 0.5-1.0 parts of calcium fluoride.

[0008] In one embodiment, the material includes, by weight, 13.5 parts of potassium feldspar, 20 parts of talc, 12 parts of sericite, 22.7 parts of china clay, 23.5 parts of kaolin, 6 parts of black mud, 0.9 parts of wollastonite, 1.4 parts of dolomite and 0.5 parts of calcium fluoride.

[0009] In one embodiment, the material includes, by weight, 13.5 parts of potassium feldspar, 20 parts of talc, 12 parts of sericite, 22.7 parts of china clay, 23.5 parts of kaolin, 6 parts of black mud, 1 part of wollastonite, 1.3 parts of dolomite and 0.7 parts of calcium fluoride.

[0010] In one embodiment, the material includes, by weight, 13.5 parts of potassium feldspar, 20 parts of talc, 12 parts of sericite, 22.7 parts of china clay, 23.8 parts of kaolin, 6 parts of black mud, 0.5 parts of wollastonite, 1.5 parts of dolomite and 1 part of calcium fluoride.

[0011] On the other hand, the present application also provides a method for manufacturing the above-mentioned sanitary ceramics, comprising: Weigh each component; The components are mixed, ground, sieved, and water glass and water are added to adjust the specific gravity to 1.77-1.79 to obtain an initial slurry; pouring the initial slurry into a mold and drying it to obtain a green body; The green body is glazed and fired in an oxidizing atmosphere for at least 20 hours to obtain the sanitary ceramic.

[0012] In one embodiment, the grinding comprises grinding each component until particles with a particle size of <10 μm account for 58-62 wt %; or 325 mesh residue is <4 wt %.

[0013] In one embodiment, the sintering includes heating to 600°C for 5 hours, then heating to 1100°C for 5 hours, then heating to a range of 1200°C-1230°C for 1.5 hours, keeping the temperature for 0.5 hours, and then cooling to room temperature for 8 hours.

[0014] In yet another aspect, the present application also provides use of calcium fluoride in reducing the number of pores in sanitary ceramic glaze, comprising adding 0.5-1 parts by weight of calcium fluoride to 100 parts by weight of raw materials for preparing a green body of sanitary ceramic.

[0015] In one embodiment, the method further includes glazing the body and firing it in an oxidizing atmosphere, wherein the firing includes heating the body to 600°C for 5 hours, then heating the body to 1100°C for 5 hours, then heating the body to a range of 1200°C-1230°C for 1.5 hours, keeping the temperature for 0.5 hours, and then cooling the body to room temperature for 8 hours.

[0016] The present application does not limit the composition of the glaze. The present application can adopt sanitary ceramics, such as ceramic tiles, ceramic toilets and other commonly used glaze materials.

[0017] The present application introduces calcium fluoride into the raw materials for preparing sanitary ceramic green bodies and controls the temperature gradient of the firing process, thereby utilizing the fact that calcium fluoride begins to react and decompose into active calcium oxide at a relatively low temperature (e.g., around 600°C); active calcium oxide easily reacts with sulfur-containing impurities (e.g., pyrite, etc.) in the green body raw materials to form calcium sulfide, which in turn reacts with oxygen at high temperatures to release sulfur dioxide, thereby allowing the sulfides in the green body to react completely before the glaze melts (e.g., at around 1100°C), without generating sulfide gas that breaks through the glaze surface or stays in the glaze to form glaze pores after the subsequent glaze melts.

[0018] The present application introduces calcium fluoride into the raw materials for preparing the sanitary ceramic body and controls the temperature gradient of the firing process, thereby advancing the reaction time of sulfide impurities and extending the sulfide reaction time. Therefore, the sulfides in the body can react completely before the glaze melts, and will not release gas at high temperature to produce pores.

[0019] The method for reducing glaze pores of the present application is easy to operate and is particularly suitable for double-sided glazed sanitary ceramics, and can significantly reduce the number of pores in the double-sided glaze.

[0020] The method of the present application can be applied to situations where the FeS2 (calculated as SO2) impurity content in the raw materials for preparing the sanitary ceramic body is relatively high, such as when the FeS2 (calculated as SO2) impurity content is between 0.2wt% and 0.5wt%. This can maximize the utilization of these raw materials of poor quality and generate extremely high economic and social benefits.

[0021] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0023] Figure 1 The following are photos showing the appearance of sanitary ceramic tiles manufactured in various embodiments and comparative examples of the present application. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present application more clear, the embodiments of the present application are described in detail below. It should be noted that the embodiments and features in the embodiments of the present application can be combined with each other arbitrarily without conflict.

[0025] Unless otherwise specified, the materials used in the following examples and comparative examples are commercially available.

[0026] The present application provides a method for manufacturing sanitary ceramics, comprising weighing each component; mixing and grinding the components, screening them, and adding water glass and water to adjust the specific gravity to 1.77-1.79 to obtain an initial slurry; pouring the initial slurry into a mold, drying it to obtain a green body; glazing the green body and firing it in an oxidizing atmosphere for 20 hours to obtain the sanitary ceramics.

[0027] In the present application, the sintering may include heating to 600°C for 5h, then heating to 1100°C for 5h, then heating to the range of 1200°C-1230°C for 1.5h, keeping the temperature for 0.5h, and then cooling to room temperature for 8h.

[0028] The following uses sanitary ceramic tiles as an example to describe the method for manufacturing sanitary ceramics of the present application, which may specifically include: 1. Forming slurry: Add the weighed components into the ball mill and grind until the particles with a particle size of less than 10μm account for 58-62wt%. After exiting the mill, add water glass and water through a 100-mesh sieve and adjust the specific gravity to 1.77-1.79, flow rate V0: 35~50s, flow rate V30: 60-80s to obtain the initial slurry; 2. Forming ceramic brick samples: pouring the initial slurry into a gypsum mold with a size of 15×15×1.4 cm in length, width and thickness, with a slurry absorption time of 90 min, opening the mold and drying to obtain a brick body; 3. Repair and cleaning: Use a blade to scrape and smooth the surface of the blank and the surrounding area, polish it with a scouring pad, and then use a wet sponge to wipe off the dust on the surface; 4. Glazing: Place the processed body flat on a stand, use a wet sponge that has been wrung out of water to add water to the glazed surface, then pour the glaze evenly on the body surface, and when the glaze surface is 0.8-1.0mm, stand up the test brick to allow the floating glaze on the surface to flow away; after the water sheen on the glaze surface disappears, remove the body, smooth the edges and corners, and place the body on the stand with the newly glazed surface as the bottom, and glaze the other side. When both sides are glazed and fired, the gas decomposed at high temperature will not escape from the unglazed surface due to the small resistance of the unglazed surface, but will escape evenly, forming pores on the glazed surface; 5. Firing test: Place unglazed test strips on both ends of the glazed body and fire it in a tunnel kiln to obtain tiles with detected pores.

[0029] Table 1 below shows the dosage of each raw material component used in Examples 1 to 3 and Comparative Examples 1 to 3 for manufacturing sanitary ceramic tiles of the present application, wherein potassium feldspar can be Fujian potassium feldspar, Guangxi potassium feldspar, etc.; porcelain clay can be high-strength porcelain clay, washed porcelain clay, etc.; kaolin can be Guangdong kaolin, Fujian Zhangzhou kaolin, etc.; black mud can be Qingyuan black mud, etc.

[0030] Table 1

[0031] Performance Testing 1. Visual appearance Figure 1 The appearance photos of the sanitary ceramic tiles manufactured in each embodiment and comparative example are shown, and visual observation is performed.

[0032] 2. Water absorption The water absorption of the sanitary ceramic tiles produced in each of the examples and comparative examples was tested, and the results are shown in Table 2 below.

[0033] 3. Pore statistics The pores on the front surface of the sanitary ceramic tiles manufactured in each embodiment and comparative example were marked with a marker on a test bench and the number of pores was counted. The results are also shown in Table 2 below.

[0034] Table 2

[0035] Depend on Figure 1 It can be seen from the results in Table 2 that Comparative Example 1 does not contain calcium fluoride, so the number of pores is particularly large, up to more than 100. Although Comparative Examples 2 and 3 contain calcium fluoride, they do not reach the specified amount, such as 0.5% of the total weight of other green body raw materials, so the number of pores is only slightly reduced. On the contrary, the water absorption rates of Examples 1-3 of the present application after firing are equivalent to those of Comparative Examples 1-3, which proves that the sintering state is equivalent; but the number of pores in the double-sided glaze is significantly reduced, reaching less than 10, and the glaze surface reaches a standard that is better than the single-sided glaze, and no pore defects will occur, and the overall glaze surface is in good condition.

[0036] This indicates that the calcium fluoride introduced in the present application greatly advances the time for the sulfur-containing impurities to be gasified into sulfur dioxide under a controlled heating temperature gradient, and the sulfide reaction time is correspondingly extended. The sulfides in the green body can react completely during the firing cycle, thereby significantly reducing the number of pores on the sanitary ceramic glaze.

[0037] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Those skilled in the art can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A sanitary ceramic with reduced glaze pores, characterized in that The green body of the sanitary ceramic is made of the following materials, which include, by weight, 10-20 parts of potassium feldspar, 15-25 parts of pyrophyllite, 10-20 parts of sericite, 20-30 parts of china clay, 20-30 parts of kaolin, 5-10 parts of black mud, 0.5-1.0 parts of wollastonite, 1.0-2.0 parts of dolomite and 0.5-1 parts of calcium fluoride.

2. The sanitary ceramic according to claim 1, characterized in that The materials include, by weight, 12-15 parts of potassium feldspar, 20-25 parts of pyrophyllite, 10-15 parts of sericite, 20-26 parts of china clay, 20-25 parts of kaolin, 5-10 parts of black mud, 0.5-1.0 parts of wollastonite, 1.0-1.5 parts of dolomite and 0.5-1.0 parts of calcium fluoride.

3. The sanitary ceramic according to claim 1, characterized in that The materials include, by weight, 13.5 parts of potassium feldspar, 20 parts of pyrophyllite, 12 parts of sericite, 22.7 parts of china clay, 23.5 parts of kaolin, 6 parts of black mud, 0.9 parts of wollastonite, 1.4 parts of dolomite and 0.5 parts of calcium fluoride.

4. The sanitary ceramic according to claim 1, characterized in that The materials include, by weight, 13.5 parts of potassium feldspar, 20 parts of pyrophyllite, 12 parts of sericite, 22.7 parts of china clay, 23.5 parts of kaolin, 6 parts of black mud, 1 part of wollastonite, 1.3 parts of dolomite and 0.7 parts of calcium fluoride.

5. The sanitary ceramic according to claim 1, characterized in that: The materials include, by weight, 13.5 parts of potassium feldspar, 20 parts of pyrophyllite, 12 parts of sericite, 22.7 parts of china clay, 23.8 parts of kaolin, 6 parts of black mud, 0.5 parts of wollastonite, 1.5 parts of dolomite and 1 part of calcium fluoride.

6. A method for manufacturing a sanitary ceramic according to any one of claims 1 to 5, characterized in that: include: Weigh each component; The components are mixed, ground, sieved, and water glass and water are added to adjust the specific gravity to 1.77-1.79 to obtain an initial slurry; pouring the initial slurry into a mold and drying it to obtain a green body; The green body is glazed and fired in an oxidizing atmosphere for at least 20 hours to obtain the sanitary ceramic.

7. The method according to claim 6, characterized in that The grinding comprises grinding each component until particles with a particle size of <10 μm account for 58-62 wt %; or 325 mesh residues are <4 wt %.

8. The method according to claim 6, characterized in that The sintering process includes heating to 600°C for 5 hours, then heating to 1100°C for 5 hours, then heating to a range of 1200°C-1230°C for 1.5 hours, keeping the temperature for 0.5 hours, and then cooling to room temperature for 8 hours.

9. Use of calcium fluoride in reducing the number of pores in sanitary ceramic glaze, characterized in that: The method comprises adding 0.5-1 weight part of calcium fluoride to 100 weight parts of raw materials for preparing a green body of sanitary ceramics.

10. The use according to claim 9, characterized in that The method also includes glazing the body and firing it in an oxidizing atmosphere, wherein the firing includes heating to 600°C for 5 hours, then heating to 1100°C for 5 hours, then heating to a range of 1200°C-1230°C for 1.5 hours, keeping the temperature for 0.5 hours, and then cooling to room temperature for 8 hours.

Citation Information

Patent Citations

  • Sanitary ceramics slip and preparation technology thereof

    CN105712697A

  • Preparation method of sanitary ceramics containing green body reinforcing agent

    CN106187082A

  • Daily fine ceramics of diopside

    CN1088190A

  • Matt dry granular surface rock plate and preparation method thereof

    CN113087491A

  • Self-cleaning glaze and application thereof

    CN115286249A